2016
DOI: 10.1002/advs.201600208
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Platform Containing Graphene Mesoporous Structure and Carbon Nanotube for Hydrogen Evolution

Abstract: It is of great significance to design a platform with large surface area and high electrical conductivity for poorly conductive catalyst for hydrogen evolution reaction (HER), such as molybdenum sulfide (MoSx), a promising and cost‐effective nonprecious material. Here, the design and preparation of a free‐standing and tunable graphene mesoporous structure/single‐walled carbon nanotube (GMS/SWCNT) hybrid membrane is reported. Amorphous MoSx is electrodeposited on this platform through a wet chemical process und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Another study from Zhu's group reported the electrodeposition of similar catalysts on a free-standing and binder-free hybrid membrane composed of mesoporous graphene and single-walled CNTs. [78] In such a nanostructure, the mesoporous graphene/SWCNT membrane was uniformly assembled and exhibited good flexibility, while the active sites were homogeneously distributed on its surface.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…Another study from Zhu's group reported the electrodeposition of similar catalysts on a free-standing and binder-free hybrid membrane composed of mesoporous graphene and single-walled CNTs. [78] In such a nanostructure, the mesoporous graphene/SWCNT membrane was uniformly assembled and exhibited good flexibility, while the active sites were homogeneously distributed on its surface.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…Although the Pt‐based materials have been proven to be the most efficient electrocatalysts for hydrogen evolution reaction (HER), the high cost, limited supply, and poor durability hinder their global‐scale application . Therefore, much effort has been dedicated to develop robust nonnoble‐metal HER catalysts, such as cobalt‐, nickel‐, iron‐, tungsten‐, and molybdenum‐based materials.…”
Section: Methodsmentioning
confidence: 99%
“…DOI: 10.1002/advs.201700733 most efficient electrocatalysts for hydrogen evolution reaction (HER), the high cost, limited supply, and poor durability hinder their global-scale application. [3,4] Therefore, much effort has been dedicated to develop robust nonnoble-metal HER catalysts, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] such as cobalt-, nickel-, iron-, tungsten-, and molybdenum-based materials.…”
mentioning
confidence: 99%
“…Synthesis of BGF : Fabrication and purification of GO dispersion were conducted using a modified Hummers method as done in the previous report . First, 1 wt% F127 aqueous solution was stirred vigorously with the whisk for 1 min.…”
Section: Methodsmentioning
confidence: 99%